APA Handbook of Men and Masculinities. 2016
DOI: 10.1037/14594-013
|View full text |Cite
|
Sign up to set email alerts
|

Asian American men.

Abstract: Asian Americans are the fastest growing population in the United States-growth between 2000 and 2010 was 46% (U.S. Census Bureau, 2011). The major ethnic groups among Asian Americans include Chinese (3.8 million), Filipino (3.4 million), Indian (3.2 million), Vietnamese (1.7 million), and Korean (1.7 million). Among this group, Asian American men, although heterogeneous in terms of culture and ethnicity, make up a distinct population that has been systematically marginalized and traditionally understudied. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Racial stereotypes are gendered such that Asian Americans are stereotypically considered as more feminine than Black and White people (Galinsky et al, 2013;Johnson et al, 2012;Wilkins et al, 2011). In the United States, Asian women are seen as exotic and objects of sexual desires (Hwang & Parreñas, 2021) and Asian men are seen as effeminate and asexual (Iwamoto & Kaya, 2016). As such, the larger Asian American group is seen as more feminine than other racial groups.…”
Section: Gendered Perceptions Of East and South Asian Facesmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial stereotypes are gendered such that Asian Americans are stereotypically considered as more feminine than Black and White people (Galinsky et al, 2013;Johnson et al, 2012;Wilkins et al, 2011). In the United States, Asian women are seen as exotic and objects of sexual desires (Hwang & Parreñas, 2021) and Asian men are seen as effeminate and asexual (Iwamoto & Kaya, 2016). As such, the larger Asian American group is seen as more feminine than other racial groups.…”
Section: Gendered Perceptions Of East and South Asian Facesmentioning
confidence: 99%
“…All these groups were, and continue to be, unfairly scrutinized by neighbors and the US government (Cainkar, 2018). Consequently, South Asian Americans (and men in particular) are stereotyped not only as extremely foreign but they may even be perceived as anti-American terrorists and dangerous religious extremists (Iwamoto & Kaya, 2016;Thangaraj, 2015).…”
Section: Stereotypes and Perceptions Of Asian Americansmentioning
confidence: 99%
“…Research has shown that stereotypes associated with Asian Americans are the most feminine and least masculine 2 , as compared to Blacks and Whites, who occupy an intermediate position between Asian Americans and Blacks (Galinsky et al, 2013; Wilkins et al, 2011). Specifically, research on stereotypes about Asian Americans has consistently identified attributes consistent with feminine stereotypes and those signifying a lack of masculinity—being passive, quiet, shy, non-dominant, family-oriented, and physically weak (Berdahl & Min, 2012; Ho & Jackson, 2001; Lin et al, 2005; Mukkamala & Suyemoto, 2018; Wong et al, 2012; also, see Iwamoto & Kaya, 2016 and Uchida, 1998).…”
Section: Intersectional Prototypicality Modelmentioning
confidence: 99%
“…Further, reflecting the power and privileges associated with Whiteness in U.S. society, White men and women tend to be perceived as having the “right amount” of masculinity and femininity, respectively; by contrast, men and women of color are stereotyped as having deviant levels of (i.e., excessive or too little) masculinity and femininity, respectively (Iwamoto & Kaya, 2016; Ridgeway & Kricheli-Katz, 2013). Several studies have found support for this gendered racial perspective.…”
Section: Intersectional Prototypicality Modelmentioning
confidence: 99%
See 1 more Smart Citation